IMPLEMENTATION OF HIGH-SPEED MICROPROCESSOR BACKUP POWER SOURCES AT AN INDUSTRIAL ENTERPRISE - Федорів, Михайло; Гладь, Іван; Бацала, Ярослав (SWorldJournal, 2024)
The paper considers the problems of ensuring the reliability of electricity supply. The implementation of microprocessor-based high-speed automatic reserve input is proposed.